Urban Rehabilitation: A Glimpse from the Spatial Planning Law - Virtudes, Ana L. (2019)
The urbanized policy of the last years in Portugal has been based on the construction of urban expansion areas, as much for industrial ends as for residential ends. It is estimated that the areas available for construction when added to the consolidated urban areas can house a population of 30 million inhabitants, while the Portuguese population is around 10 million. Many of these new urban areas are much bigger than it is necessary with problems in terms of waste of infrastructures, creating urban voids or discontinuity. Recently, there have arisen new legal diplomas designed to encourage an urbanized praxis that goes against the current trend and incentives the urban rehabilitation actions. These diplomas define one policy of urban rehabilitation in articulation with the municipal plans, namely with the contents of the detailed local plans (the most detailed of the Portuguese planning system). In this context, this article aims to present a reflection about the new challenges to the urban rehabilitation as an agent of urban design, the figure of detailed local plan as the first instrument of urbanized praxis in urban spaces which should be hackneyed in its utilization and, the process of construction of the city based on urban rehabilitation instead of urban expansion.